2000
DOI: 10.1080/713654955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of early quantitative food restriction on long bone growth at different environmental temperatures in broiler chickens

Abstract: 1. This investigation was carried out to study the influence of early quantitative food restriction (40% of ad libitum intake from 7 to 14 d of age) and environmental rearing temperature (thermoneutral, cold and hot) on long bone (tibia, femur and humerus) development in broiler chickens. 2. Tibia, femur and humerus were obtained at the ages of 14, 21, 28, 35 and 42 d, and the variables studied were: length and width (mm, expressed as absolute values), bone breaking strength (kgf) and bone weight/bone length i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 13 publications
2
23
0
7
Order By: Relevance
“…These birds presented lower femur width, tibia and femur weight, tibia length, femur and tibia mineral content and area, and tibia shaft values. These results are consistent with the findings of Bruno et al (2000), who reported that CV: variation coeffecient. a-b: means followed by different letters in columns differ significantly by Tukey test at 5% probability.…”
Section: Effect Of In-ovo Ascorbic Acid Injection On the Bone Developsupporting
confidence: 83%
See 1 more Smart Citation
“…These birds presented lower femur width, tibia and femur weight, tibia length, femur and tibia mineral content and area, and tibia shaft values. These results are consistent with the findings of Bruno et al (2000), who reported that CV: variation coeffecient. a-b: means followed by different letters in columns differ significantly by Tukey test at 5% probability.…”
Section: Effect Of In-ovo Ascorbic Acid Injection On the Bone Developsupporting
confidence: 83%
“…Fast-growing chickens, i.e., genetically-improved broilers breeds, produce high metabolic heat and may not be able to maintain normothermia under hot environmental conditions (Bruno et al, 2000). The resulting heat stress can negatively affect bone development in these broilers breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Shank width, tibia weight, breaking strength and tibia proximal epiphysis ash in the meal-feeding group was lower compared to the control group on day 21. The effect of restriction on linear bone growth seems to be associated with chondrocyte activity (Bruno et al, 2000), as Heinrichs et al (1997) determined that a rapid depletion of growth plate chondrocytes and inhibition of longitudinal bone growth occur in food-restricted rabbits. Also our findings (at 21 days) are in agreement with earlier studies, which showed that food restriction could adversely affect bone formation in chicks (Bruno et al, 2000) and rats (Fetoui et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Su et al (1999) reported that birds fed fewer meals per day had better walking ability. Bruno et al (2000) noted that bone length and width reduced when feed was restricted to 40% of ad libitum intake in broiler from 7 to 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…Além destas diferenças genéticas, outros fatores podem influenciar o desenvolvimento ósseo das aves, tais como: idade, sexo, manejo, nutrição, temperatura (COOK, 2000;EDWARDS JUNIOR, 2000;BRUNO et al, 2000;BIZERAY et al, 2002, BRUNO et al, 2007.…”
Section: Introductionunclassified